ARTIFICIAL INTELLIGENCE AS AN INNOVATIVE TOOL FOR SHAPING CONTEMPORARY ARCHITECTURE - Karandiuk, Denys (Theory and practice of design, 2025)
The article examines artificial intelligence as an innovative tool of form-making in contemporary architecture, design, and visual arts. The study identifies its role in transforming the creative process, spatial thinking, and architectural-artistic practice. The main areas of application of neural network technologies in architecture are outlined, including generative and parametric design, interior and object design, landscape modeling, digital sculpture, and artistic practices. It is determined that the integration of artificial intelligence introduces new approaches to exploring form, structure, and composition, expands the creative capabilities of architects, enhances the efficiency of design solutions, and optimizes the stages of project development. Purpose: to identify and substantiate the role of artificial intelligence as an innovative instrument of form-making in contemporary architecture; to determine the main directions of its use in architectural, design, and artistic projects; and to analyze the influence of digital technologies on the aesthetics and structure of the architectural environment. Methodology. The research employs methods of systems analysis, comparison, synthesis, and generalization of modern scientific sources and practical experience in applying neural networks in architectural design. Results. The study identifies the key areas of artificial intelligence application in architecture: the creation of conceptual and visual models, development of spatial solutions, automation of drawing and parametric modeling processes, generation of materials and textures, and formation of landscape and sculptural compositions. Neural network algorithms contribute to improving energy efficiency, harmonizing the architectural environment, and fostering new aesthetic trends. Scientific novelty lies in the comprehensive analysis of artificial intelligence as a factor of architectural and artistic transformation. For the first time, the directions of its application in architectural form-making have been systematized, and the role of algorithmic technologies in the development of compositional and spatial solutions has been defined. This opens new perspectives for architectural design within the context of digital culture. Practical relevance. The findings can be applied in the design of modern architectural objects, educational programs in architectural modeling, digital design, and art education. The integration of AI into design practice enhances the quality of architectural solutions and contributes to the development of new professional competencies among architects.